Lean Accounting in Textile and Garment Industry: Comparative Study and its Impact on Firm Performance - Swatdikun, Trairong; Phonnikornkij, Naphaphorn (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
Operation effectiveness is a key element that drives modern management techniques to support waste elimination in accounting procedures. Lean accounting supports procedures to enhance lean manufacturing which focuses on transpose of manufacturing value to customers. Lean accounting requires supportive analysis and measurement, recording, and reporting financial information that appropriately responds to executive needs. This paper aims to compare the implementation of lean accounting among textile and garment firms. It also explores the impact of lean accounting on firm performance. The results reveal that different firm types, total assets, and number of employees have different implications on analyzing and measurement aspects, recording aspects, and reporting aspect value. Furthermore, lean accounting implementation on the recording aspect has a direct impact on financial and non-financial performance, while the reporting aspect only has a direct impact on non-financial performance.